(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: This study aims to compare performance of conventional phenotypic Löwenstein–Jensen (LJ) -drug susceptibility testing (DST) and GeneXpert for the detection of Mycobacterium tuberculosis against Rifampicin (RIF) susceptibility assay from smear positive TB patients in the South Punjab region. Methods: A total of4809 sputum samples were collected from 16 districts of South Punjab consecutively of newly enrolled and already diagnosed pulmonary TB patients. RIF susceptibility was performed by Phenotypic drug susceptibility testing in parallel with GeneXpert at Provincial TB Reference Laboratory (PRL) in collaboration with Pathology Department, Nishtar Medical College (NMC), Multan. Results: The final analysis was performed among 4544 (96.68%) cases from enrolled 4809 cases which include 3805 (83.74%) new and 739 (16.26%) on treatment patients. Among them, 4222 (92.91%) cases were susceptible (RIF) while 322 (7.09%) were resistant to Rifampicin. The valid RIF susceptibility testing result was available from substantially more cases with GeneXpert 4400 (96.83%)than with phenotypic DST 4273 (94.04%). Discordant 40 results included 21(0.51%) MTB+RIF ‘S’ on phenotypic LJ-DST and ‘R’ on GeneXpert and 19(0.46%) MTB+RIF ‘R’ on phenotypic LJ-DST and ‘S’ on GeneXpert. This difference (0.97%) was less significant. Conclusions: This study concluded that the GeneXpert assay had 98.9% specificity in detecting susceptibility to Rifampicin in TB patients. The use of this assay is a feasible option for treating and controlling the tuberculosis in this regional settings.